2019
DOI: 10.2147/dddt.s207315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Jatrorrhizine inhibits colorectal carcinoma proliferation and metastasis through Wnt/β-catenin signaling pathway and epithelial–mesenchymal transition</p>

Abstract: Purpose Jatrorrhizine (JAT) is a natural protoberberine alkaloid, possesses detoxification, bactericidal and hypoglycemic activities. However, its anti-cancer mechanism is not clear. This study aimed to investigate the mechanism of JAT through which inhibits colorectal cancer in HCT-116 and HT-29 cells. Methods MTT assay and colony formation assay were used to check the cell proliferation ability. Cell apoptosis and cell cycle were measured by Hoechst 33342 staining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…The effect of β-catenin and EMT on cell apoptosis has been reported 34 , 35 , but the role of DNER in epirubicin-induced apoptosis has not been studied. DNER and β-catenin were expressed in an epirubicin concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of β-catenin and EMT on cell apoptosis has been reported 34 , 35 , but the role of DNER in epirubicin-induced apoptosis has not been studied. DNER and β-catenin were expressed in an epirubicin concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CK18 was identified as a target gene of miR-325-3p, suggesting that miR-325-3p is associated with the degree of EMT in CRC. EMT is widely involved in the invasion and metastasis of colon cancer due to the loss of epithelial characteristics into mesenchymal cells ( 24 , 25 ). The results of the present study demonstrated that high miR-325-3p expression significantly decreased the expression of the epithelial marker, CK18, but increased the expression levels of the mesenchymal markers, vimentin and α-SMA.…”
Section: Discussionmentioning
confidence: 99%
“…APS inhibits EMT by suppressing the activity of the Wnt/β-catenin signaling pathway. The Wnt signaling pathway is an important classical pathway in eMT (17). The present study investigated whether aPS exerted its antitumor effect by suppressing the activity of the Wnt/β-catenin signaling pathway.…”
Section: Aps Inhibits Breast Cancer Cell Invasion Invasion Is Anmentioning
confidence: 97%
“…Previous studies demonstrated that a variety of factors can induce eMT, including transforming growth factor β (TGF-β), Wnt, Notch and fibroblast growth factor (13)(14)(15)(16). among these inducers, the Wnt/β-catenin signaling pathway, which can be divided into classical and non-classical signaling pathways, has attracted increasing attention (17). Wnt has been identified as the promoter of the pathway (18) and, as an upstream factor, β-catenin affects the expression of downstream factors of the signaling pathway, including c-Myc and cyclin d1 (19).…”
Section: Introductionmentioning
confidence: 99%